Marx the Fichtean - Rockmore, Tom (ETHICS IN PROGRESS, 2021)
We ignore the history of philosophy at our peril. Engels, who typically conflates Marx and Marxism, points to the relation of Marxism to the tradition while also denying it. In his little book on Feuerbach, Engels depicts Feuerbach as leading Marx away from Hegel, away from classical German philosophy, away from philosophy and towards materialism and science. This view suggests that Marx is at best negatively related to Classical German philosophy, including Hegel. Yet Engels elsewhere suggests that Marx belongs to the classical German philosophical tradition. In the preface to Socialism, Utopian and Scientific, Engels wrote: “We German socialists are proud that we trace our descent not only from Saint Simon, Fourier and Owen, but also from Kant, Fichte and Hegel” (Marx & Engels, Collected Works). In this paper I will focus on Marx’s relation to Fichte. This relation is rarely mentioned in the Marxist debate, but I will argue, it is crucial for the formulation of Marx’s position, and hence for assessing his contribution accurately. One of the results of this study will be to indicate that Marx, in reacting against Hegel, did not, as is often suggested, ‘leave’ philosophy, but in fact made a crucial philosophical contribution.